2011
DOI: 10.4049/jimmunol.1003897
|View full text |Cite
|
Sign up to set email alerts
|

Somatically Diversified and Proliferating Transitional B Cells: Implications for Peripheral B Cell Homeostasis

Abstract: The peripheral B cell compartment in mice and humans is maintained by continuous production of transitional B cells in the bone marrow (BM). In other species however, including rabbits, B lymphopoiesis in the BM abates early in life and it is unclear how the peripheral B cell compartment is maintained. We identified transitional B cells in rabbits and classified them into T1 (CD24hiCD21lo) and T2 (CD24hiCD21+) B cell subsets. By neutralizing BAFF in vivo, we found an arrest in peripheral B cell development at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…B cell shuttling of ICs and subsequent transfer of ICs to FDCs in mouse lymph nodes are dependent on complement, requiring C3 deposition on ICs, and B cell and FDC expression of the complement receptors CD21/35 (39, 41). Consistent with a similar B cell shuttling of bacterial cells in rabbit GALT, Yeramilli and Knight (42) observed C3 deposition in the follicles of conventional, but not germ-free ligated, appendix, and further found that lumenal bacteria were coated with C3 and IgA. Blocking CD21 binding/signaling with a CD21-Ig fusion protein and depleting C3 with cobra venom factor both inhibited B cell proliferation, demonstrating that antibody repertoire diversification in rabbit GALT is dependent on complement.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…B cell shuttling of ICs and subsequent transfer of ICs to FDCs in mouse lymph nodes are dependent on complement, requiring C3 deposition on ICs, and B cell and FDC expression of the complement receptors CD21/35 (39, 41). Consistent with a similar B cell shuttling of bacterial cells in rabbit GALT, Yeramilli and Knight (42) observed C3 deposition in the follicles of conventional, but not germ-free ligated, appendix, and further found that lumenal bacteria were coated with C3 and IgA. Blocking CD21 binding/signaling with a CD21-Ig fusion protein and depleting C3 with cobra venom factor both inhibited B cell proliferation, demonstrating that antibody repertoire diversification in rabbit GALT is dependent on complement.…”
Section: Discussionsupporting
confidence: 54%
“…CCR7 might therefore act as a “default” receptor, mediating B cell migration to the B cell:T cell boundary after downregulation of CCR6 and CXCR5. Although antibody repertoire diversification in GALT is T cell-independent, in the sense of not being driven by cognate B cell-T cell interactions (35, 42), our results suggest that T cells contribute to the process. This is consistent with the observation that, during early follicle development, B cell proliferation occurs in the region of the follicle immediately adjacent to the T cell area (9, 12).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The mouse and other animal models provide important insights into human B cell development and disease (1, 2). Murine data show that B lineage committed progenitors arise from hematopoietic stem cells in the bone marrow (BM) and transit a series of developmentally sequential stages to produce immature B cells expressing surface IgM (3, 4).…”
Section: Introductionmentioning
confidence: 99%